(untitled) (Journal of Applied Learning and Teaching, 2020)
For many students today, ‘going to uni’ requires attending classes, but also juggling work and family commitments. In response to these changing needs, and the increasing importance of digital interaction, most universities now offer blended learning, supplementing face-to face classes with online learning. The present study examined student perceptions of what they put into, and gain from, blended classes. Third-year psychology undergraduates (n = 130) at an Australian university rated their experience of tutor-directed, face-to-face practical classes, and self-directed, online practical classes, in the one academic unit. In quantitative terms, students reported that they invested similar amounts of effort into the two class modalities, but learned slightly more from face-to-face than online classes. In qualitative terms, students gave contrasting reasons for their perceived learning in the two modalities. They appreciated the classroom experience for the chance to ask questions and revise content, and the online experience for its need for independent thought, although they also missed personal discussion. Responses also showed that different students experienced the two modalities in quite different ways. Judiciously combining in-class and online learning activities, with student choice where possible, seems a relatively efficient way to help enhance the university experience of today’s busy students.